POWER PLUG-METER - Haifa Sairy; Nour Khreim (My University, 2011)
With the ever-rising cost of electricity, we're all getting increasingly sensitive about how much power our computers, televisions, appliances and other products are using - not just when we're using them, but also when they're allegedly turned off.Some, like refrigerators, aren't running full tilt all the time. Others, such as computers, printers, displays and other gear, have "sleep" modes, they power down significantly but they're still on. And some devices, like televisions and cable boxes, aren't really off when we push that "Off" button or switch. All are still drawing a small amount of power, a phenomenon that's called "parasitic load." Power plug-meter: Its a device which can measure, in real time and have the facilities to output and represents various aspects of AC power. It can also act as a computer-controlled remote switch.A power plug meter, which also called a "plug load meter" sits in between the power outlet and an individual device and displays how much power (load) the connected device is consuming at the moment.